Potentials of speech disorders correction in 4-6 yrs children by means of ergo and art therapy - N. B. Petrenko; M. M. Filippov (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Purpose: to work out methodic of speech disorders correction in 4-6 yrs children by ergo and art therapy means. Material: during academic year three groups of children (n=97) were being observed: two groups - with speech disorders (control and main) and one group of healthy children. Psycho-motor and cognitive functions were assessed with the help of tests for motor coordination (speed of their fulfillment, verbal thinking). Results: it was found that characteristic feature of such children is critical estimation of own speech insufficiency and conscious avoiding oral answers. By cluster analysis results increase of homogeneity in psycho-physical condition's positive changes, cognitive functions and dance abilities resulted from dance-correction training program were shown. Conclusions: the worked out dance-correction choreographic trainings helps in the following: developing rhythm sense; strengthening of skeleton and muscles; memory, attention, thinking and imagination simulation. Acquiring of such experience will help a child to further successfully train different art-creative and sports kinds of activities; to master choreography and gymnastic as well as different musical instruments.